Dog Man and Cat Kid - Pilkey, Dav 1966-; Garibaldi, Jose (2018)
When a new sitter arrives and a movie star goes missing, Dog Man and Cat Kid investigate, but Petey, the world's most evil cat, complicates their case.
"Treehouse Comix proudly presents."
Chiefly illustrations
$9.99
Keywords: Dogs -- Comic books, strips, etc; Cats -- Comic books, strips, etc; Dogs -- Juvenile fiction; Cats -- Juvenile fiction; Dogs -- Fiction; Cats -- Fiction; Adventure and adventurers -- Fiction; Humorous stories; Graphic novels; Dogs -- Fiction; Cats -- Fiction; Humorous comics; Graphic novels